2022
DOI: 10.3389/fmed.2022.840702
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Cryobiopsy vs. Forceps Biopsy for Interstitial Lung Diseases, Lung Tumors, and Peripheral Pulmonary Lesions: An Updated Systematic Review and Meta-Analysis

Abstract: BackgroundCryobiopsy has emerged as a novel alternative to conventional forceps biopsy for the diagnosis of interstitial lung diseases (ILDs), lung tumors, and peripheral pulmonary lesions (PPLs). This study aims to compare cryobiopsy and forceps biopsy for the diagnosis of these lung pathologies with respect to efficacy and safety by performing a meta-analysis of updated evidence.MethodsA number of databases, such as PubMed, Embase, Web of Science, the Cochrane Library, OVID, CNKI, and Wanfang database, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(65 reference statements)
2
4
0
Order By: Relevance
“…There were two instances of minor bleeding, both rated 2 or lower on the Nashville Bleeding Scale. Our findings are in line with previous meta-analysis comparing the safety profiles of cryoprobe and forceps, suggesting that the use of a cryoprobe does not increase the risk of bleeding during PPL biopsies [14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There were two instances of minor bleeding, both rated 2 or lower on the Nashville Bleeding Scale. Our findings are in line with previous meta-analysis comparing the safety profiles of cryoprobe and forceps, suggesting that the use of a cryoprobe does not increase the risk of bleeding during PPL biopsies [14].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that cryobiopsy provides larger tissue samples, fewer artifacts, and higher diagnostic yield when compared to traditional transbronchial forceps in diffuse lung diseases [12, 17]. In individuals with PPLs, a recently updated systematic review and meta-analysis revealed that cryoprobes provided higher diagnostic yield over forceps in 9 out of the 13 studies [14]. Griff et al [7] conducted a morphometrical analysis comparing cryoprobe and forceps in transbronchial biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumothorax occurred in 10% of our cohort, similar to previously published rates in systemic reviews and meta-analyses [4,8,[15][16][17]. TBCB was not a risk factor for pneumothorax or chest tube placement, as was shown in previous studies [23,29,30]. Our cohort's 6% bleeding rate is lower than most other large-scale studies [9,16,24,31,32].…”
Section: Transbronchial Biopsy For Interstitial Lung Diseasessupporting
confidence: 89%
“…Transbronchial cryobiopsy (TBCB) is useful a biopsy technique in diagnosing interstitial lung disease (ILD) and lung tumors, as it can collect a sufficient number of specimens without crush damage 4,5) . Although TBCB has a higher risk of bleeding than forceps biopsy 6) , adequate hemostasis can be achieved endoscopically. In ILD diagnosis, it was reported that TBCB specimens combined with various clinical findings might avoid invasive surgical lung biopsy 7,8) .…”
Section: Introductionmentioning
confidence: 99%